2014
DOI: 10.1111/gwao.12054
|View full text |Cite
|
Sign up to set email alerts
|

‘Dirt, Death and Danger? I Don't Recall Any Adverse Reaction …’: Masculinity and the Taint Management of Hospital Private Security Work

Abstract: Drawing on an ethnographic narrative written by one of the authors following his resignation from a hospital private security team in Ottawa, Canada and interview data gleaned from eight security men (all former colleagues), this article explores how hospital private security officers draw on discourses of masculinity to navigate the 'dirty' boundaries of their work, and to preserve their alpha-guard statuses as controlled, autonomous and authoritative subjects. We found that hospital guards manage and deflect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 37 publications
(80 reference statements)
1
43
0
Order By: Relevance
“…More recently, starting from the original theorization proposed by Hughes (, ), social psychologists and anthropologists focused their research on occupational dirt and identity dynamics (e.g., Ashforth & Kreiner, ; Ashforth, Kreiner, Clark, & Fugate, , ; Bosmans et al ., ; Cassell & Bishop, ; Filteau, ; Johnston & Hodge, ; Kreiner, Ashforth, & Sluss, ; Meldgaard Hansen, ; Selmi, ). For example, Dick () explained that being branded as a ‘dirty worker’ may imply a significant threat to the identity goal of seeing themselves in a positive light.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, starting from the original theorization proposed by Hughes (, ), social psychologists and anthropologists focused their research on occupational dirt and identity dynamics (e.g., Ashforth & Kreiner, ; Ashforth, Kreiner, Clark, & Fugate, , ; Bosmans et al ., ; Cassell & Bishop, ; Filteau, ; Johnston & Hodge, ; Kreiner, Ashforth, & Sluss, ; Meldgaard Hansen, ; Selmi, ). For example, Dick () explained that being branded as a ‘dirty worker’ may imply a significant threat to the identity goal of seeing themselves in a positive light.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the awarding of security guard licenses to individuals with criminal records raises important policy questions. Unarmed security guards do not carry weapons and are not law enforcement agents; given that many positions are not highly paid, can involve unorthodox schedules, and may not be held in high esteem by the public, some might consider the occupation to be undesirable “dirty work” (Johnston and Hodge, ). Yet the job involves protecting people and property and has gained some legitimacy through a growing recognition of private security as part of the “extended police family” (Thumala, Goold, and Loader, : 294).…”
mentioning
confidence: 99%
“…Empirical work has supported and extended these arguments (e.g., Ashforth, Kreiner, Clark, & Fugate, ; Bosmans et al, ; Cassell & Bishop, ; Dick, ; Filteau, ; Johnston & Hodge, ; Meldgaard Hansen, ; Selmi, ). For example, Bosmans et al () document the use of ideologies, supporting supporters, and condemning condemners in a study of domestic workers; Dick () describes how police officers absolve themselves of the moral ambiguity surrounding the use of coercive force against citizens; and Selmi () found that phone sex workers resisted negative labeling and cast their work in socially acceptable terms through “identity cleansing.” Note, however, that this research has seldom examined the role of the dirty work manager , a potentially important player in the adjustment process.…”
Section: Introductionmentioning
confidence: 92%